Don't know responses to cognitive and affective risk perception measures: Exploring prevalence and socio‐demographic moderators. Issue 2 (2nd February 2018) - Janssen, Eva; Verduyn, Philippe; Waters, Erika A.
Abstract : Objectives: Many people report uncertainty when appraising their risk of cancer and other diseases, but prior research about the topic has focused solely on cognitive risk perceptions. We investigated uncertainty related to cognitive and affective risk questions. We also explored whether any differences in uncertainty between cognitive and affective questions varied in magnitude by item‐specific or socio‐demographic characteristics. Design: Secondary analysis of data collected for a 2 × 2 × 3 full‐factorial risk communication experiment ( N  =   835) that was embedded within an online survey. Methods: We investigated the frequency of 'don't know' responses (DKR) to eight perceived risk items that varied according to whether they assessed (1) cognitive versus affective perceived risk, (2) absolute versus comparative risk, and (3) colon cancer versus 'any exercise‐related diseases'. Socio‐demographics were as follows: sex, age, education, family history, and numeracy. We analysed the data using multilevel logistic regression. Results: The odds of DKR were lower for affective than cognitive perceived risk (OR = 0.64, p  < .001). This difference occurred for absolute but not comparative risk perceptions (interaction effect, p  = .004), but no interactions for disease type or demographic characteristics were found ( p s > .05). Conclusions: Lower uncertainty for affective (vs. cognitive) absolute perceived risk items is consistent with research stating: (1) Risk perceptions are grounded in people's feelings about a hazard, and (2) feelings are easier for people to access than facts. Including affective perceived risk items in health behaviour surveys may reduce missing data and improve data quality. Statement of contribution What is already known on this subject? Many people report that they don't know their risk (i.e., risk uncertainty). Evidence is growing for the importance of feelings of risk in explaining health behaviour. Feelings are easier for people to access than facts. What does this study add? Don't know responding is higher for absolute cognitive than absolute affective risk questions. This difference does not vary in magnitude by demographic characteristics. Affective perceived risk questions in surveys may reduce missing data and improve data quality.